SOCIAL ASPECTS OF URBANIZATION DEVELOPMENT IN SOUTHERN UZBEKISTAN (Scientific journal of the Fergana State University, 2024)
In the article, the social aspects of the development of urbanization processes are studied on the example of Southern Uzbekistan. Based on the purpose, the relationship between the network, composition and hierarchy of regional cities and the service sector is revealed. That is, the development of social spheres, together with serving the growth of cities, urban areas have collected the most important and largest set of services based on the population.To study the influence of social spheres in the development of urbanization processes, to analyze the qualitative and quantitative expansion of service networks in accordance with the hierarchy of cities, to study social spheres as a city-forming factor in the case of Southern Uzbekistan, setting the goals and objectives of the work will give.The methodological basis of the article is a complex approach, in which methods such as geographical comparison, system-content, historical, statistical, mathematical, territorial analysis are used. The research work was carried out based on the analysis of data from statistical departments of Surkhandarya and Kashkadarya regions, as well as special scientific literature and cartographic sources.Areas of public service - trade, education, health care system are located in settlements, that is, in central places, at different levels. Each of these places has its own unique influence and scope of service. In this regard, cities are considered to be the center of the complex of social spheres of that region, in addition to performing the function of a specific administrative (provincial and district centers) and economic (large industrial production facilities, transport hubs) "capital".